The Effectiveness of TikTok Social Media Content in Improving Students' Understanding of Islamic Religious Education in Grade X at SMK N 1 Batealit - Setiawan, M. Bagus; Taufiqurrahman, Taufiqurrahman (At- Ta'lim : Jurnal Pendidikan, 2025)
This study aims to analyze the effectiveness of TikTok social media content as a learning medium in improving students' understanding of Islamic Religious Education (PAI) subjects for grade X at SMK N 1 Batealit. The rapid growth of TikTok users in Indonesia, which will reach 157.6 million in 2024, and its potential as an interactive learning tool. The method used is quantitative with an experimental design Pretest-Posttest Control Group Design, involving 32 students as the experimental group (using TikTok) and 32 students as the control group (using textbooks). Data were collected through an understanding test and analyzed statistically with normality, homogeneity, and T-test tests. The results showed a significant increase in the experimental group, with an average posttest score of 92.03, much higher than the control group (77.34). In addition, the consistency of students' understanding in the experimental group was also better, indicated by a lower standard deviation (5,800) and a narrow range of values (80-100). Hypothesis testing confirmed that TikTok was statistically more effective in improving students' understanding (Sig. < 0.001). The conclusion of this study is that TikTok can be an effective learning medium for Islamic Religious Education, especially in attracting interest and improving students' understanding. The implication is that educators are advised to utilize digital platforms such as TikTok with relevant and educational content designs, in order to create more interactive learning that is in accordance with the characteristics of the digital generation.